Cyclic behaviour of CLT shear wall hold-down connections using mixed angle self-tapping screws. (1st July 2023) - Wright, Thomas; Li, Minghao; Moroder, Daniel; Lim, Hyungsuk; Carradine, David
Highlights: Thirty high-capacity mixed angle screw hold-down connections were tested. Mixed angle screws can provide a strong, stiff, and ductile hold-down connection. Current design methods provide a conservative prediction for strength. Abstract: This paper experimentally examines structural performance of novel cross laminated timber (CLT) hold-down connections consisting of customised steel brackets and self-tapping screws installed with mixed angles relative to loading. The installation of screws at mixed angles combines the high strength and stiffness of inclined screws with the high ductility of 90° screws creating a strong, stiff, and ductile connection. A total of 30 high capacity connection specimens comprising two timber species and five connection configurations are tested under monotonic and cyclic loading. The ratios between inclined screws and 90° screws are investigated in order to optimise the connection seismic performance. Connections consisting of 12× Ø12 mm inclined screws and 12 to 24× Ø12mm / 10 mm 90° screws were found to demonstrate high ultimate strength (470–593 kN), high initial stiffness (212–269 kN/mm) and high ductility (µ=10–20) under cyclic loading. Current strength calculation methods for the connection design are compared to the experimental results and are shown to provide conservative design predictions.